Copyright Law As Collateral Under Pawn And Fiduciary Schemes: A Perspective Based On Dsn-Mui Fatwa No. 25 Of 2002 On Rahn And Dsn-Mui Fatwa No. 68 Of 2008 On Rahn Tasjily - Elina Adi Wijayanti (Jurnal Ilmiah Multidisiplin, 2025)
Collateral is a fundamental requirement in credit transactions, both in conventional and Islamic banking and financial institutions. However, with the advancement of the times, it becomes necessary to examine the legal framework governing the use of copyright as collateral under a pawn scheme. Furthermore, how can copyright be utilized as collateral in credit transactions in accordance with both positive law and Islamic law? This study adopts a normative-empirical approach, analyzing regulations related to intellectual property rights—particularly copyright—and secured transactions such as Law No. 28 of 2014 on Copyright, Bank Indonesia Regulation No. 9 of 2007 on Bank Credit Collateral, and the DSN-MUI Fatwa No. 68 of 2008 on Rahn Tasjily. The findings of this study indicate that under the Copyright Law, copyright can indeed serve as collateral in credit transactions, but only through the fiduciary scheme. In practice, however, both conventional and Islamic banks have not yet fully implemented copyright-based collateral due to the absence of specific regulations that comprehensively govern such practices.